Numerical Simulation of Hydrodynamic Pressure on Bridge Pier in Water for a Model Test. Issue 1 (March 2020) - Qin, Yifang; Tao, Xiaxin; Tao, Zhengru; Liu, Haiming
Abstract: Finite element model with considering the fluid and structure interaction is built by software ADINA with the same conditions of a shaking table model test in this paper. The hydrodynamic pressures at 7 submerged depths on the water-pier interfaces, as the same positions the sensors fixed in the test, are calculated from motion inputs E1 with PGA of 0.2651g and E2 with PGA of 0.51g numerically in two direction combinations. The result shows that the pressures from the simulation and the test are close to each other, and means that the numerical procedure adopted in this paper is feasible to take into account the water-pier interaction, while the test results are also validated by the simulation.